(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Vocational education is increasingly attaining enormous significance in our nation of lately. The absence of professional capability as a result of the current educational framework has offered ascend to the requirement for ability based educational schemes. It is in this setting this study is conducted to ponder the present situation, issues and put forward conceivable proposals for the Vocational Education segment in India. The general point of this research paper is to consider the present situation and issues of Vocational education in India and to derive specific conclusions regarding administration framework which can currently bind together and streamlines this sector of education in India. Both primary and secondary data is collected for the research. The primary is collected through a self-administered questionnaire survey. The data is collected from Total 14 vocational training institutes in Nagpur district.